Effects of Planting Density and Weeding Frequency on the Corn Growth and Yield in Intercropping System with Peanut - Welmi Samita; Edhi Turmud; Sigit Sudjatmiko; Widodo Widodo (TERRA : Journal of Land Restoration, 2021)
The research aimed to determine the optimal population ratio at each frequency of weeding for the growth and yield of maize. It was carried out from February to May 2020 in the field. There are 2 treatment factors tested arranged in a splite plot design, which was repeated 3 times using a completely randomized block design (CRBD). The first factor is the frequency of weeding as the main plot (Main Plot) consisting of no weeding, 1 x weeding (21 DAS), 2 x weeding (21 DAS and 42 DAS). The second factor is the ratio of the population as sub-plots, consisting of 100% corn + 0% peanuts, 80% corn + 20% peanuts, 60% corn + 40% peanuts, 40 % corn + 60% peanuts, 20% corn + 80% peanuts. The results showed that the growth and yield of maize in the intercropping system with peanuts gave the same response to the population ratio at all weeding frequencies. The planting density of 40% maize + 60% peanuts produced the highest response on the variables of stem diameter (24.675 mm), plant fresh weight (667.51 grams) and biomass weight (79.924 grams). While the highest response to weeding frequency was 2 times (21 DAS and 42 DAS) only on plant fresh weight (588.08 grams).